Bubble clustering in a horizontal turbulent channel flow investigated by bubble-tracking velocimetry. (November 2019) - Oishi, Y.; Tohge, Y.; Tasaka, Y.; Murai, Y.
Highlights: Bubble clustering patterns in horizontal wall turbulence are visualized. Two dimensional bubble probability density and local relative motions are obtained. Streamwise attraction, lateral repulsion, and tandem circulation are quantitatively extracted. The clustering is somewhat enhanced due to size deviation of bubbles due to turbulent shear. Abstract: We investigated bubble clustering in a horizontal turbulent channel flow experimentally. Accurate image processing was used to detect individual bubble centroids with a 100% success rate. The successful detections realize bubble tracking velocimetry for Lagrangian mapping of bubble-bubble interaction both visually and quantitatively. The bubble-bubble interaction becomes explicit as the channel Reynolds number ( Re ) increases in the range 5, 000 <  Re  < 11, 000, incorporating streamwise attraction, lateral repulsion, and tandem circulation within a space narrower than 3 bubble diameters. We attribute this to the turbulent boundary layer where wall-sliding bubbles display streamwise velocity differences due to size. The resulting clustering can be attributed to poly-dispersed bubbles. This idea is verified by experimental data classified by bubble size. The present findings offer an explanation for the initiation of void waves in a bubbly two-phase boundary layer at a scale larger than that of the original coherent structures involved in the turbulence.